P3007 Time course of the response to ACTH in pig: biological and transcriptomic study. (1st September 2016) - Sautron, V.; Terenina, E.; Gress, L.; Lippi, Y.; Billon, Y.; Villa-Vialaneix, N.; Mormede, P.
Abstract: The hypothalamic–pituitary–adrenal (HPA) axis plays a major role in physiological homeostasis. It is also involved in stress and adaptive response to the environment. In farm animals in general and more specifically in pigs, breeding strategies have highly favored production traits such as lean growth rate, feed efficiency and prolificacy at the cost of robustness. On the hypothesis that the HPA axis could contribute to the trade-off between robustness and production traits, we have designed this experiment to explore individual variation in the biological response to the main stress hormone, cortisol, in pigs. We used adrenocorticotropic hormone (ACTH) injections to trigger production of cortisol in 120 juvenile Large White (LW) pigs from 28 litters, and the kinetics of the response was measured with biological variables and whole blood gene expression at four time points. A multilevel statistical analysis was used to take into account the longitudinal aspect of the data. Cortisol level reached its peak 1 h after ACTH injection. White blood cell composition was modified with a decrease of lymphocytes and monocytes and an increase of granulocytes ( FDR < 0.05). Basal level of cortisol was correlated with birth and weaning weights. Microarray analysis identified 65 unique genes whose expression responded to the injection of ACTH (adjusted P-value < 0.05). These genes were classified into four clusters with distinctive kinetics in response to ACTH injection. The first cluster identified genes strongly correlated to cortisol and previously reported as being regulated by glucocorticoids. In particular, DDIT4, DUSP1, FKBP5, IL7R, NFKBIA, PER1, RGS2 and RHOB were shown to be connected to each other by the glucocorticoid receptor NR3C1. Most of the differentially expressed genes that encode transcription factors have not been described yet as being important in transcription networks involved in stress response. Their co-expression indicates possible co-regulation, and they potentially provide new biomarkers of sensitivity to cortisol.